CONTROLE DE DRENAGEM ÁCIDA DE MINA DE CARVÃO POR MEIO DE WETLANDS CONSTRUÍDOS - Ribeiro, Thiago Henrique (2021)
Acid mine drainage - AMD is characterized as a significant environmental impact resulting from coal mining, which must be properly treated so as not to cause major damage to natural resources. In the ambit of passive treatments from AMD, constructed wetlands stands out for being a technology of easy operation and low cost. In view of the above, the present research aimed to evaluate the performance of two vertical flow constructed wetlands (VFCW) on a microcosm scale, operated in batches, for the treatment of acid mine drainage from coal mining waste piles. The support medium was composed by a basal layer of limestone or granite and a layer of organic compound, formed by sandy soil, bovine manure and pine bark. The macrophyte used in the two wetlands was Typha, known as Taboa. The treatment systems were evaluated based on the increase in pH, the reduction of acidity and the efficiency of removing iron and manganese in the effluents after the 24-hour hydraulic detention period. In addition, a statistical comparison was made between the results obtained in the two different types of CWs. The calcite-based wetland (CCW) showed a pH increase higher than the granite-based wetland (GCW), whose highest average increase was from 2,8 to 5,8. The highest values in terms of acidity reduction were 76,9% in the CCW and 63,8% in the GCW. There was no statistically significant difference between the two treatment systems in terms of metal removal, with iron and manganese removal efficiencies reaching, in that order, levels of 60,9% and 49,3% in the treatment system composed of limestone and 59,0% and 45,0% in that built with granite. Thus, the applicability of constructed wetlands in the treatment of acid mine drainage has been proven. However, for effluents with very low pH values and with a high concentration of metals, it is emphasized that this technology should be used as an alternative combined with other types of treatment.